Sales and distribution management : an Indian perspective - Venugopal, Pingali, 1958- (Response Books ; Sage Publications, 2008)
Though India has become a lucrative market for various companies, the unique characteristics of its market throw up a variety of challenges. Sales and Distribution Management:. An Indian Perspective aims to understand these challenges. Building on an understanding of the consumer decision process, the book defines the roles of marketing and selling strategies. Secondly adopting a customer-centric approach to sales and distribution management, the book deals with making strategic decisions keeping the end consumer in mind and making operational decisions.